Pediatric Stroke Rates Over 17 Years: Report From a Population-Based Study. (June 2018) - Lehman, Laura L.; Khoury, Jane C.; Taylor, J. Michael; Yeramaneni, Samrat; Sucharew, Heidi; Alwell, Kathleen; Moomaw, Charles J.; Peariso, Katrina; Flaherty, Matthew; Khatri, Pooja; Broderick, Joseph P.; Kissela, Brett M.; et al.
We previously published rates of pediatric stroke using our population-based Greater Cincinnati Northern Kentucky Stroke Study (GCNK) for periods July 1993–June 1994 and 1999. We report population-based rates from 2 additional study periods: 2005 and 2010. We identified all pediatric strokes for residents of the GCNK region that occurred in July 1, 1993–June 30, 1994, and calendar years 1999, 2005, and 2010. Stroke cases were ascertained by screening discharge ICD-9 codes, and verified by a physician. Pediatric stroke was defined as stroke in those <20 years of age. Stroke rates by study period, overall, by age and by race, were calculated. Eleven children died within 30 days, yielding an all-cause case fatality rate of 15.7% (95% confidence interval 1.1%, 26.4%) with 3 (27.3%) ischemic, 6 (54.5%) hemorrhagic, and 2 (18.2%) unknown stroke type. The pediatric stroke rate of 4.4 per 100 000 in the GCNK study region has not changed over 17 years.